Three new species of triplefin blennies of the genus Enneanectes (Teleostei, Tripterygiidae) from the tropical eastern Pacific with a key to Pacific species of Enneanectes - Rosenblatt, Richard H.; Miller, Elizabeth C.; Hastings, Philip A. (Zootaxa, 2013)
Three new species of the triplefin blenny genus Enneanectes found in the Pacific Ocean off southern Mexico are de-scribed. Two, Enneanectes glendae and Enneanectes macrops, are mainland species, while the third, Enneanectes exsul, is endemic to the Islas Revillagigedo. A key to the five species of Enneanectes known from the tropical eastern Pacific is provided.